Detection of numerical chromosome anomalies in interphase cells of benign and malignant thyroid lesions using fluorescence in situ hybridization - Barril, N.; Carvalho-Sales, A. B.; Tajara, E. H. (Elsevier B.V., 2000)
Benign and malignant thyroid tumors constitute a wide range of neoplasias showing recurrent chromosome abnormalities. In an attempt to characterize specific numerical chromosome abnormalities in thyroid tissues, We present here the findings from a study of archival samples depicted by 10 malignant tumors, 30 benign lesions, and 10 normal thyroid tissues. Fluorescence in situ hybridization was performed on noncultured samples using biotinylated centromere-specific probes for chromosomes 7, 10, and 17. Trisomy or tetrasomy 7 were present in 19 benign and in 7 malignant tumors. Trisomy 10 or 17 were observed in 18 adenomas or goiters and in 9 carcinomas, and monosomy 17 was seen in 2 carcinomas. Our findings suggest that such abnormalities are an in vivo phenomenon and may be important in the neoplastic proliferation of thyroid gland. (C) Elsevier B.V., 2000. All rights reserved.